(untitled) (Education in the 21st Century, 2023)
The main goal of the educational process in a flying higher military educational institution is the formation of high professional skills and a creative approach to solving combat missions among graduates. The nature of the actions of the crews and tactical aviation units in modern conditions of performing combat missions requires military pilots to have a high level of professional intelligence, operational-tactical thinking, and the ability to navigate correctly in a rapidly changing air tactical situation. The implementation of these requirements is ensured by training (the formation of knowledge and skills), the development of professionally essential qualities, psychological training, as well as the use of appropriate forms, methods and techniques of training of future military pilots of tactical aviation to perform combat missions. It is this aspect that requires the improvement of traditional forms and methods of air tactical training in the educational process, as well as the search and implementation of new ones.